Staying Together or Breaking Apart: Policy-makers' Endogenous Coalitions Formation in the European Economic and Monetary Union - Bas van Aarle; Giovanni Di Bartolomeo; Jacob Engwerda; Joseph Plasmans (Center for Economic Studies and ifo Institute (CESifo), 2002)
In this paper, we analyze coordination of macroeconomic stabilization policies within the EMU by focusing, in a dynamic set-up, on asymmetries, externalities, and the existence of a multi-country context. We study how coalitions among fiscal and monetary authorities are formed and what are their effects on the stabilization of output and price. In particular, our attention is directed to study the consequences on these issues of different institutional contexts in which policy-makers may act. Among other results, we found that, in the presence of externalities, the occurrence of asymmetries is a necessary but not a sufficient condition for cooperation.
Keywords: 330; macroeconomic stabilization; EMU; coalition formation.